2018
DOI: 10.1038/s41598-018-23482-4
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based discovery of mPGES-1 inhibitors suitable for preclinical testing in wild-type mice as a new generation of anti-inflammatory drugs

Abstract: Human mPGES-1 is recognized as a promising target for next generation of anti-inflammatory drugs without the side effects of currently available anti-inflammatory drugs, and various inhibitors have been reported in the literature. However, none of the reported potent inhibitors of human mPGES-1 has shown to be also a potent inhibitor of mouse or rat mPGES-1, which prevents using the well-established mouse/rat models of inflammation-related diseases for preclinical studies. Hence, despite of extensive efforts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 48 publications
0
40
0
1
Order By: Relevance
“…In summary, we have characterized, in the present study, five new cross‐species mPGES‐1 inhibitors suitable for p.o delivery with improved potency and selectivity compared to published inhibitors lacking interspecies differences (Ding et al, ; Leclerc, Idborg, et al, ; Leclerc, Pawelzik, et al, ). All five compounds presented comparable selectivity and potency.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In summary, we have characterized, in the present study, five new cross‐species mPGES‐1 inhibitors suitable for p.o delivery with improved potency and selectivity compared to published inhibitors lacking interspecies differences (Ding et al, ; Leclerc, Idborg, et al, ; Leclerc, Pawelzik, et al, ). All five compounds presented comparable selectivity and potency.…”
Section: Discussionmentioning
confidence: 82%
“…We have previously characterized mPGES‐1 inhibitors lacking interspecies differences in murine models of inflammation (Leclerc, Idborg, et al, ; Leclerc, Pawelzik, et al, ) as well as in cancer models (Kock et al, ; Olesch et al, ) and recently Ding et al () described new cross‐species inhibitors, but there is still a need for further improved mPGES‐1 inhibitors for preclinical investigations. New mPGES‐1 inhibitors are required to have superior affinity and improved bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Human mPGES-1 is recognized as a promising target for the next generation of anti-inflammatory drugs, without the side effects of those currently available (Ding et al, 2018). Our hypothesis, that selective mPGES-1 inhibition might attenuate COVID-19 associated disease symptoms, e.g.…”
Section: Selective Mpges-1 Inhibition To Attenuate Covid-19 Associatementioning
confidence: 90%
“…Today mPGES-1 is considered as a potential safer target for anti-inflammatory drugs since it is only expressed in diseased tissues and downstream of the COX enzymes (Ding et al, 2018). COX enzymes are the current target of most commercially available non-steroidal anti-inflammatory drugs (NSAIDs, COX inhibitors).…”
Section: Pge2 In Inflammationmentioning
confidence: 99%
“…It has been reported that both aspirin and celecoxib synergize with anti-PD-1 blockade in mouse models of melanoma and colorectal cancer (18). Comparisons between human, rat and mouse mPGES1 show structural differences in their active site that suggest more selective mouse inhibitors are needed to achieve the same degree efficacy when combined with PD-1 in a syngeneic mouse setting (47,48). This prompted us to perform KO of mPGES1 in syngeneic melanoma cells to achieve the same effects as aspirin or celecoxib.…”
Section: Elevated Mpges1 Expression Is Associated With Low Cd8 þ T-cementioning
confidence: 99%